Penciptaan Batik Prada Berbasis Ornamen Batak Toba Dengan Teknik Batik Tulis - Raysyah Daulay; Sri Wiratma; Raden Burhan SN. Diningrat (Universitas Palangka Raya, 2025)
The creation of batik Prada based on Toba Batak ornaments with written batik technique is motivated as a form of expression and cultural preservation. The ornaments used in the design of this Prada batik are adapted from Toba Batak ornamental motifs, namely gorga. This research aims to create and realize the results of Prada batik based on Toba Batak ornaments with written batik. The creation method used in the creation of batik works has three stages of methods, namely exploration, design, and realization. These three stages can be broken down into six steps. The creation of Prada batik works based on Toba Batak ornaments with written batik techniques, realized into 12 works with a size of 105 x 200 cm. The results of this research show that the application of Toba Batak ornaments in Prada batik creates works that have high artistic value and can preserve the art of batik. The results of the findings on the application of gold Coloring to batik Toba Batak ornaments with written batik technique, serves to give the impression of luxury and can emphasize the lines in certain motifs without changing the meaning and philosophy contained in each Toba Batak ornament.